2019
DOI: 10.1128/jvi.00336-19
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of Bluetongue Virus NS3 Protein in Regulation of the MAPK/ERK Signaling Pathway

Abstract: Bluetongue virus (BTV) is an arbovirus transmitted by blood-feeding midges to a wide range of wild and domestic ruminants. In this report, we showed that BTV, through its nonstructural protein NS3 (BTV-NS3), is able to activate the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway, as assessed by phosphorylation levels of ERK1/2 and the translation initiation factor eukaryotic translation initiation factor 4E (eIF4E). By combining immunoprecipitation of BTV-NS3 and mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Further, prime-boost intramuscular vaccination of sheep with a pentavalent cocktail of DISA vaccines for the “European” serotypes 1, 2, 3, 4, and 8 based on the same DISA platform protects against virulent BTV2 or 8, suggesting that sheep are protected for all five serotypes (van Rijn et al personal communication) (Figure 4). Lack of NS3/NS3a protein likely enhances the interferon mediated immune response, since NS3/NS3a counteracts the innate immune response, and in particular the type I interferon (IFN-α/β) pathway by different mechanisms (162164).…”
Section: Vaccinesmentioning
confidence: 99%
“…Further, prime-boost intramuscular vaccination of sheep with a pentavalent cocktail of DISA vaccines for the “European” serotypes 1, 2, 3, 4, and 8 based on the same DISA platform protects against virulent BTV2 or 8, suggesting that sheep are protected for all five serotypes (van Rijn et al personal communication) (Figure 4). Lack of NS3/NS3a protein likely enhances the interferon mediated immune response, since NS3/NS3a counteracts the innate immune response, and in particular the type I interferon (IFN-α/β) pathway by different mechanisms (162164).…”
Section: Vaccinesmentioning
confidence: 99%
“…Moreover, NS3 closely associates with newly synthesized progeny viruses, and subsequent studies have shown that NS3 is involved in the virus budding process [13,15,18,19]. Recently, it has been shown that NS3 also plays a role in supporting virus replication, by activating the MAPK/ERK signaling pathway [20].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond cell exit, NS1 plays the role of a positive regulator of viral protein synthesis in infected cells. In addition to its role in cell exit [65], NS3 is involved in interferon antagonism [70].…”
Section: Discussionmentioning
confidence: 99%